The Na+ -Coupled Glucose Transporter SGLT2 Interacts with its Accessory Unit MAP17 in Vitro and Their expressions overlap in the renal proximal tubule - Calado, J (2019)
Na+ -glucose cotransporter 2 is the renal Na+ -coupled glucose transporter responsible for the tubular glucose reabsorption, while MAP17 was recently identified as its accessory unit. Mutations in either of the proteins' coding genes, SLC5A2 and PDZK1IP1, lead to urinary glucose excretion. To investigate whether MAP17 interacts with SGLT2 in vitro, we engineered a V5-tagged SGLT2 construct and evaluated HEK293T cells coexpressing it together with a HA tagged MAP17 construct. MAP17 is shown to colocalize and coimmunoprecipitate with SGLT2. Also, in human kidney sections, the expression of both proteins overlaps at the apical surface of tubular epithelia. This interaction provides the rationale behind SGLT2 activation by MAP17 as well the similarity of the SLC5A2 and PDZK1IP1 glucosuric phenotypes.